Young Adults With Pancreatic Cancer: National Trends in Treatment and Outcomes. Issue 3 (March 2020) - Alese, Olatunji B.; Jiang, Renjian; Shaib, Walid; Wu, Christina; Akce, Mehmet; Gaines, Tyra; Ni, Liang; Behera, Madhusmita; El-Rayes, Bassel F.
Abstract : Objectives: The treatment and outcomes of patients younger than 50 years (young adults [YAs]) with pancreatic cancer are largely unknown. We evaluated the presentation, treatment, and outcomes of these patients. Methods: The National Cancer Database was analyzed. Univariate and multivariate Cox proportional hazards models were performed to identify variables associated with overall survival. Results: A total of 124, 442 patients with pancreatic cancer were identified, with 9657 between 18 and 50 years of age. Mean age was 45.4 years (standard deviation, 4.6 years). About 30.9% of YA patients and 25% of patients older than 50 years underwent resection of the primary tumor. Survival advantage was seen for patients 18 to 39 years (hazard ratio, 1.14; 95% confidence interval, 1.07–1.23; P < 0.001). This age advantage was similar across all the racial groups. Overall, YAs treated between 2009 and 2013 had higher survival rates compared with 2004 to 2008 (hazard ratio, 0.85; 95% confidence interval, 0.81–0.89; P < 0.001). This survival improvement was highest in American Indians and Asian/Pacific Islanders (16.6% vs 6.5%), African Americans (10.6% vs 8.5%), and Hispanics (14.5% vs 12.6%). Conclusions: Survival of YAs with pancreatic cancer patients is superior to older patients and has improved over time, especially in minority populations.